Ingredients of gender-based stereotypes about food. Indirect influence of food type, portion size and presentation on gendered intentions to eat. (1st August 2015) - Cavazza, Nicoletta; Guidetti, Margherita; Butera, Fabrizio
Highlights: This study examines the dimensions of gendered stereotypes about food. A small portion fosters a feminine association to the dish. An elegant presentation fosters a feminine association to the dish. A feminine association to the dish fosters women's (vs men's) intention to eat it. Women were more influenced than men by gendered stereotypes about food. Abstract: The association between certain foods and masculinity or femininity has been widely discussed in different disciplines. However, extant research has yet to clarify which are the critical dimensions lending these gender connotations to food and thus impacting on the willingness to eat it. We present a study on the role of food type, portion size, and dish presentation as potential factors constituting the gender-based stereotype about food, and their indirect or mediated effect on the intention of men and women to eat certain feminine/masculine stereotyped foods. We manipulated the three features cited above in a 2 (food type: Caprese vs. hamburger) × 2 (portion size: small vs. big) × 2 (presentation: elegant vs. rough) full factorial design. Results confirmed a model of moderated mediation: the Caprese salad, the small portion and the elegantly presented dish (in respect to the hamburger, the big portion and the roughly presented dish) tend to be considered "feminine food", and thus women expressed a more pronounced intention to eat it than men. The implications of the findings for both theory and practice are discussed.